\[\boxed{\text{358\ (358).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ 7x \cdot (x - 4) - x \cdot (6 - x) =\]
\[= 7x^{2} - 28x - 6x + x^{2} =\]
\[= 8x^{2} - 34x.\]
\[\boxed{\text{358.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ \left( 3a^{2}b \right)^{2} = 3^{2} \cdot \left( a^{2} \right)^{2} \cdot b^{2} =\]
\[= 9a^{4}b^{2}\]
\[2)\ \left( 16x^{6}y^{7}z^{8} \right)^{2} =\]
\[= 16^{2} \cdot \left( x^{6} \right)^{2} \cdot \left( y^{7} \right)^{2} \cdot \left( z^{8} \right)^{2} =\]
\[= 256x^{12}y^{14}z^{16}\]
\[3)\ \left( - \frac{1}{5}c^{6}d \right)^{4} =\]
\[= \left( - \frac{1}{5} \right)^{4} \cdot \left( c^{6} \right)^{4} \cdot d^{4} =\]
\[= \frac{1}{625}c^{24}d^{4}\]